Implementasi Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PKn di SMA Negeri 1 Batukliang Utara - Akbar, Akbar (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aim of this research was to implement a Problem-Based Learning model to improve student learning outcomes at SMAN 1 Batukliang Utara. This research was a classroom action research with three cycles consisting of four stages, namely planning, acting, observing, and reflecting. The subjects of this study were students of class XII MIA 2 consisting of 20 students. Research instruments used were: (1) Lesson Plan implementation observation sheets, (2) students response questionnaires, and (3) learning outcomes tests. Data analysis techniques used descriptive statistical analysis in the form of percentage completeness and students learning outcomes. The results of the study showed that the implementation of a problem-based learning model could improve the students learning outcomes of class XII MIA 2 at SMAN I Batukliang Utara Central Lombok Regency.